SMS messages for changing farmer behavior - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
An sms online platform has been set up in Uganda which has potential to be used for further messaging. An evaluation was successful. Data analysis is ongoing on whether or not it changed practices. Identifying and drafting messages was evidence based. There's however no platform for pig farmers until now.